A Contribution for the Understanding of Meals Consumption in Restaurants under a Sociological Point of View - Paula, Nilma Morcef de; Dencker, Ada de Freitas Maneti (Review of Business Management, 2007)
Meals consumed in restaurants assume an increasingly important role due to lifestyle changes. This research compares the results from a study carried out with a group of under-graduate students from a university in The United Kingdom with results from another study with post-graduate students in Brazil, both of which refer to the identification of the most marking aspects of an unforgettable meal. The application of qualitative methodology intends to be the first step towards defining the categories that may be used in wider-ranging studies, directed towards restaurant management, considering, in a preliminary way, the criteria studied by Lashley, Morrinson and Randall (2004): occasion, company, atmosphere, food, service and environment, added to the factors of time and the outstanding fact of the event. The study revealed the importance of atmosphere and environment in the symbolic construction of an evaluation in eating habits in restaurants where, in some cases, may surpass the importance attributed to the food. Key-words: Consumer behavior. Restaurant. Sociology of food.